Cross-cultural counseling: problems and prospects - Repetto, Elvira (2002)
This work tries to assess the contributions made to educational counseling in recent years by theoretical and applied research and practical actions in the area of cross-cultural counseling. So, it offers a synthesis of the main contributions made from the theoretical and practical viewpoints within this specific scientific field.